2006
DOI: 10.3171/jns.2006.104.5.713
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a neurointensivist on outcomes in patients with head trauma treated in a neurosciences intensive care unit

Abstract: The institution of a neurointensivist-led team model had an independent, positive impact on patient outcomes, including a lower NICU-associated mortality rate and hospital LOS, improved disposition, and better chart documentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 24 publications
4
82
2
1
Order By: Relevance
“…Varelas et al reported that a neurointensivist-led team model showed a 4% relative reduction of the in-hospital mortality rate and improved documentation of the GCS score (from 60.4% to 82%) in head injury patients. 4 Mirski et al also found that introducing a team to ICUs that is specifically trained for neuroscience critical care decreased mortality from 36% to 19% and increased the proportion of good outcomes in patients with intracranial hemorrhage from 48% to 69%. 5 Compared with these reports, our patients in both groups had much lower mortality rates (0.96%) and much improved neurological outcomes (complication rates were \ 5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varelas et al reported that a neurointensivist-led team model showed a 4% relative reduction of the in-hospital mortality rate and improved documentation of the GCS score (from 60.4% to 82%) in head injury patients. 4 Mirski et al also found that introducing a team to ICUs that is specifically trained for neuroscience critical care decreased mortality from 36% to 19% and increased the proportion of good outcomes in patients with intracranial hemorrhage from 48% to 69%. 5 Compared with these reports, our patients in both groups had much lower mortality rates (0.96%) and much improved neurological outcomes (complication rates were \ 5%).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In addition, it has been reported that utilization of a neurointensive care unit team decreased mortality rates, shortened hospital length of stay, and improved patient outcomes in the neurological and neurosurgical populations. 4,5 Collectively, it is conceivable that intensive care has a significant impact on critically ill patient outcomes. However, it has not been determined whether intensive care based on continuous monitoring (electrocardiogram (ECG), blood pressure, and pulse oximetry [SpO 2 ]) and frequent neurologic evaluation by ICU staff has a significant impact on elective neurosurgical patient outcome in those who are in good physical condition.…”
Section: Résumémentioning
confidence: 99%
“…Interestingly, the degree of heterogeneity in results was considerably less (I 2 9 and 51%, respectively). Additional benefits ascribed to neurointensivist-led teams have been reported; these include reductions in length of stay [6,9,10,[13][14][15][16], cost savings [6,19], less need for ventriculoperitoneal shunts in SAH patients [13], improved documentation [20] and increased organ and tissue donation rates [21]. Delays in transfer of patients from the emergency department to the neurocritical care unit have also been associated with worse outcomes [22].…”
mentioning
confidence: 99%
“…We identified 12 studies, involving 24,520 patients, which presented original data comparing models of care for critically ill neurologic patients [3][4][5][6][7][8][9][10][11][12][13][14]. Four studies assessing subgroups derived from previously published data were excluded (see Electronic Supplementary Material) [15][16][17][18].…”
mentioning
confidence: 99%
“…Se procederá al ingreso precoz en UCI 9 . Se controlará estrictamente: temperatura, glucemia, crisis comiciales y sepsis (control metabólico inicial).…”
Section: Medidas Generalesunclassified